Cannabis-related episodic memory deficits and hippocampal morphological differences in healthy individuals and schizophrenia subjects - Smith, Matthew J.; Cobia, Derin J.; Reilly, James L.; Gilman, Jodi M.; Roberts, Andrea G.; Alpert, Kathryn I.; Wang, Lei; Breiter, Hans C.; Csernansky, John G. (Hippocampus, 2015)
ABSTRACT Cannabis use has been associated with episodic memory (EM) impairments and abnormal hippocampus morphology among both healthy individuals and schizophrenia subjects. Considering the hippocampus' role in EM, research is needed to evaluate the relationship between cannabis‐related hippocampal morphology and EM among healthy and clinical groups. We examined differences in hippocampus morphology between control and schizophrenia subjects with and without a past (not current) cannabis use disorder (CUD). Subjects group‐matched on demographics included 44 healthy controls (CON), 10 subjects with a CUD history (CON‐CUD), 28 schizophrenia subjects with no history of substance use disorders (SCZ), and 15 schizophrenia subjects with a CUD history (SCZ‐CUD). Large‐deformation, high‐dimensional brain mapping with MRI produced surface‐based representations of the hippocampus that were compared across all four groups and correlated with EM and CUD history. Surface maps of the hippocampus were generated to visualize morphological differences. CON‐CUD and SCZ‐CUD were characterized by distinct cannabis‐related hippocampal shape differences and parametric deficits in EM performance. Shape differences observed in CON‐CUD were associated with poorer EM performance, while shape differences observed in SCZ‐CUD were associated with a longer duration of CUD and shorter duration of CUD remission. A past history of CUD may be associated with notable differences in hippocampal morphology and EM impairments among adults with and without schizophrenia. Although the results may be compatible with a causal hypothesis, we must consider that the observed cannabis‐related shape differences in the hippocampus could also be explained as biomarkers of a neurobiological susceptibility to poor memory or the effects of cannabis. © 2015 Wiley Periodicals, Inc.